PROPOSITION FOR THE ALIGNMENT OF THE INTEGRATED MANAGEMENT SYSTEM (QUALITY, ENVIRONMENTAL AND SAFETY) WITH THE BUSINESS STRATEGY - Barbosa, Luis Cesar F. M. [UNESP]; Oliveira, Otavio Jose de [UNESP]; Santos, Gilberto (Univ Montenengro, Center Quality, 2018)
With the current globalized and increasingly competitive organizational scenario, organizations increasingly need strategies to survive in the midst of excessive competition. In order to optimize efforts and resources, the companies, especially industrial companies, started to develop their own Integrated Management System (IMS), namely, quality management system, environmental management system and safety management system, among others, as a plausible and efficient alternative in this sense. However, few companies are aware of the difficulties in aligning their IMS as a strategy. This paper is classified as qualitative, and has used the bibliographic research method for its execution. Therefore, the aim of this paper is formulate the propositions that assist the IMS alignment as a business strategy. The results of this paper allow identify that really exists an interaction in both senses, i.e., the IMS influences a strategy and the strategy influences the IMS. The main contribution of this article is to support in the development based on the articulation of the IMS-related theory and business strategy.
Keywords: Integrated Management System; Business Strategy; Alignment